Overtraining or burnout: a training and psycho-behavioural case study - Main, L. C.; Landers, G. J. (International Journal of Sports Science and Coaching, 2012)
The aim of this article is to present case study data that challenges the popular conception that athlete burnout represents the ultimate outcome of overtraining. A young male triathlete (22 yrs) completed a comprehensive training diary, along with the Athlete Burnout Questionnaire (ABQ) and the Multi-component Training Distress Scale (MTDS) weekly from the commencement of pre-season training, until the end of the competitive season 45 weeks later. Results were analysed retrospectively upon completion of the season and followed up with semi-structured interviews with the coach and athlete. These longitudinal observations are the first to document an athlete who appears to have simultaneously become overtrained and developed athlete burnout as measured by the ABQ. Thus we are advocating a need for future research to clarify differences between these two training-stress syndromes, specifically in relation to their aetiology, to avoid misdiagnosis and to ensure appropriate treatment for athletes experiencing these conditions is provided.